Dynamic Systems and Control 2002
DOI: 10.1115/imece2002-32668
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Telerobotic System to Assist Persons With Disabilities

Abstract: This paper describes the development of intelligent mapping from a haptic user interface to a remote manipulator to assist individuals with disabilities performing manipulation tasks. This mapping, referred to an assistance function, is determined on the basis of environmental model or sensory data to guide the motion of a telerobotic manipulator while performing a given task. Human input is enhanced rather than superseded by the computer. Three manual dexterity assessment tests commonly used in occupational t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…They developed a.force, assistance function -that "modifies the operator's commands using a set of fuzzy rules to reduce contact force and improve surface tracking-ability.*. Pernalete et al' [14] used a force assistance function to control a teleoperation system for assisting persons with disabilities.…”
Section: Two Three and Four-channel Architecturesmentioning
confidence: 99%
“…They developed a.force, assistance function -that "modifies the operator's commands using a set of fuzzy rules to reduce contact force and improve surface tracking-ability.*. Pernalete et al' [14] used a force assistance function to control a teleoperation system for assisting persons with disabilities.…”
Section: Two Three and Four-channel Architecturesmentioning
confidence: 99%
“…Pernalete et al [11][12][13] demonstrated the application of assistance function strategies like virtual constraints and scaling on a telerobotic system that augments the performance of motion-impaired users. It allowed the users with disabilities to perform complex tasks, reduce their execution times and increase their operational accuracy.…”
Section: Introductionmentioning
confidence: 98%